Pengaruh Profitabilitas, Growth Opportunity, dan Leverage Terhadap Earnings Response Coefficient (ERC) - Aulia, Yusvita; Taqwa, Salma (Universitas Negeri Padang, 2025)
This research purpose to examine how the effect of profitability, growth opportunity, and leverage on earnings response coefficient. The companies used as the population in this research are banking companies listed on Indonesia Stock Exchange in 2020-2022. The sample was determined by using a purposive sampling method with the total sample obtained being 32 companies. The data analysis technique in this study used multiple linear regression analysis using the SPSS 27 program. Result of the analysis carried out, this research found that profitability and leverage have a significant effect on earnings response coefficient, while growth opportunity has no significant effect on earnings response coefficient. For further research, its hope that researchers will choose other variables that have an effect on earnings response coefficient.